IMU-Free UWB-Based Single Anchor Localization System - Oh, Eunseob; Park, Jiwoong; Ko, Young Bae (Journal of Korean Institute of Communications and Information Sciences, 2024)
Wireless technology-based positioning systems have become integral in location measurement and service provision across various sectors, including mobile and IoT environments. In particularly, Ultra-Wideband (UWB) technology is noted for its capacity to deliver accurate positioning performance. Positioning systems generally rely on multiple anchors; however, recent studies are investigating the feasibility of single-anchor systems. Most research in this area concentrates on using additional sensors to track the movement of tags and ascertain their locations. This paper suggests a novel approach that utilizes only a single anchor without the need for extra sensors. This method calculates the velocity of the tag using distance data, compensates for Angle of Arrival (AoA) inaccuracies, and determines its position. The experimental results indicate that this approach, employing a single anchor and no additional sensors to correct AoA, outperforms techniques that use Inertial Measurement Units (IMUs) in terms of positioning accuracy.
Keywords: AoA; Communication; EKF; Localization; Single Anchor; UWB